The Development of Economic Learning Model through CTL (Contextual Teaching and Learning) to Promote Students’ Critical Thinking Skill - Sudarmiani Sudarmiani (BIRCU, 2020)
This study aimed to describe the economic learning model that has been used in Islamic Senior High School 2 Madiun, the development of economic learning models through the CTL (Contextual Teaching and Learning) approach, and the results of research and development in economic learning model through the CTL (Contextual Teaching and Learning) approach to improve students' critical thinking skills. This study was research and development with the ADDIE approach which consists of Analysis, Design, Development, Implementation, and Evaluation. Based on the result of the analysis stage, the economic learning in Islamic Senior High School 2 Madiun was relatively conventional and yet using innovative models in economic learning. So then the innovation in the economic learning model aimed to improve students' critical thinking skills which still relatively low. Based on the results of preliminary studies and development stage, the design of economic learning models through the CTL (Contextual Teaching and Learning) approach is more effective and innovative in implement the economic learning process, especially in improving students' learning outcomes and critical thinking skills in Islamic Senior High School 2 Madiun.